2023
DOI: 10.3390/mi14020494
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall Effect of Double-Index Cylindrical Vector Beams in a Tight Focus

Abstract: We investigate the spin angular momentum (SAM) of double-index cylindrical vector beams in tight focus. Such a set of beams is a generalization of the conventional cylindrical vector beams since the polarization order is different for the different transverse field components. Based on the Richards-Wolf theory, we obtain an expression for the SAM distribution and show that if the polarization orders are of different parity, then the spin Hall effect occurs in the tight focus, which is there are alternating are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…A comparison of Equations ( 22) and (23) indicates that the helicity changes sign in approximately the same areas of the focal spot at which the spin density changes sign, since both quantities depend on sin(mϕ). In any case, with the terms with I 0,0 I 0,m contribute the most [13], and the magnitudes h and S z have the same sign. The difference is, in particular, that the expression for the helicity in (22) includes the longitudinal component of the electric field, whereas the spin density in (23) includes only the transverse components of the electric field.…”
Section: Helicity At the Focus Of A Cylindrical Vector Beammentioning
confidence: 89%
See 4 more Smart Citations
“…A comparison of Equations ( 22) and (23) indicates that the helicity changes sign in approximately the same areas of the focal spot at which the spin density changes sign, since both quantities depend on sin(mϕ). In any case, with the terms with I 0,0 I 0,m contribute the most [13], and the magnitudes h and S z have the same sign. The difference is, in particular, that the expression for the helicity in (22) includes the longitudinal component of the electric field, whereas the spin density in (23) includes only the transverse components of the electric field.…”
Section: Helicity At the Focus Of A Cylindrical Vector Beammentioning
confidence: 89%
“…It can be shown that the full helicity, averaged over the beam cross-section, equals zero and conserves upon focusing. Indeed, as shown in [13], the following expression holds:…”
Section: Helicity At the Focus Of A Linearly Polarized Optical Vortexmentioning
confidence: 99%
See 3 more Smart Citations